BAURAN PEMASARAN MAGGOT BSF (Black Soldier Fly) DI DINAS KETAHANAN PANGAN DAN PERTANIAN KOTA SURAKARTA - Nur Hidayah, Fitria; Antriyandarti, Ernoiz (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2022)
Waste management, especially in the regions, is a challenge for the government. Areas that have dense populations and limited availability of land for waste processing make there a solution to overcome this. One of the waste that has not been treated properly in urban areas is organic waste. Therefore, the cultivation of BSF (Black Soldier Fly) larvae as a decomposer of organic waste can be a solution to reduce organic waste while increasing people's income through marketing BSF larvae as animal feed. One of the government institutions that conducts education, cultivation, and marketing of BSF larvae is Food Security and Agriculture Department of Surakarta City. Study aims to determine the marketing mix of BSF larvae in the Food Security and Agriculture Department of Surakarta City by using a descriptive method. The results showed that there are 7 factors that influence the marketing mix, namely product, price, promotion, place, people, process and physical evidence. The problem faced is that because BSF larvae are marketed alive, in the distribution process they must have special treatment. Fresh BSF larvae also have a short time before turning into pre-pupae. In addition, not many people are familiar with BSF larvae as an alternative feed for fish and poultry.